Endovascular management of chronic mesenteric ischemia: a single centre experience in Western Rajasthan, India - Sarda, Pawan; Kumar, Goutam; Gupta, Deepak; Sanghvi, Sanjeev; Baroopal, Anil (International Journal of Research in Medical Sciences, 2017)
Background: Chronic mesenteric ischemia (CMI) or mesenteric angina is a condition characterised by inadequate blood supply to bowel as a result of stenosis affecting one or more of the three mesenteric arteries: the celiac artery (CA), the superior mesenteric artery (SMA) and the inferior mesenteric artery (IMA). Methods: Ten patients with significant lesion, treated with PTA and stenting were selected for study and were followed at 2 weeks, at 2 months then at 6 months after index procedure to see composite of symptomatic improvement, weight gain and revascularization. Results: On mesenteric angiography, significant ostial stenosis of celiac trunk and superior mesenteric artery in 5 patients, 3 patients had significant ostial stenosis of celiac trunk and ostial stenosis of inferior mesenteric artery and 2 patients had significant stenosis of superior mesenteric artery. Percutaneous transluminal angioplasty (PTA) and stenting was done, final result was good and there was no residual stenosis and dissection. After stenting patients were stable and pain free. There were no post-operative complications. Follow up was done after 2 weeks and 2 months and then at six months. There was no postprandial abdominal pain on follow up and almost all patient had gained weight in 2 months and on 6 months of follow up, no case of repeat revascularization was recorded. Conclusions: Percutaneous transluminal angioplasty (PTA) and stenting to mesenteric artery is good alternative management of CMI. In present series, all cases were susses fully revascularized without residual stenosis and dissection.